1993
DOI: 10.1002/pro.5560020312
|View full text |Cite
|
Sign up to set email alerts
|

Thioflavine T interaction with synthetic Alzheimer's disease β‐amyloid peptides: Detection of amyloid aggregation in solution

Abstract: Thioflavine T (ThT) associates rapidly with aggregated fibrils of the synthetic PjACderived peptides p( 1-28) and p(1-40), giving rise to a new excitation (ex) (absorption) maximum at 450 nm and enhanced emission (em) at 482 nm, as opposed to the 385 nm (ex) and 445 nrn (em) of the free dye. This change is dependent on the aggregated state as monomeric or dimeric peptides do not react, and guanidine dissociation of aggregates destroys the signal. There was no effect of high salt concentrations. Binding to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

67
1,840
3
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 2,144 publications
(1,916 citation statements)
references
References 19 publications
67
1,840
3
6
Order By: Relevance
“…30 By monitoring the kinetics of HEWL fibril formation by fluorescence spectroscopy, we found that the relative fluorescence of HEWL increased with extended incubation times (Figure 2A), which is in agreement with previous studies. 31 The consistent increase in ThT fluorescence intensity observed when HEWL was incubated alone, demonstrates that formation of amyloid fibrils proceeded rapidly and without a lag phase ( Figure 2A To determine an effective concentration range of myricetin for inhibiting HEWL fibril formation, varying aliquots of myricetin were mixed with HEWL to final concentrations of 1, 10, and 100 μM; at these concentrations we did not observe significant toxic effects of myricetin on cell survival (data not shown) and the ThT fluorescence intensity measured ( Figure 2B). Myricetin (and quercitin control) was observed to exhibit a dosedependent effect on HEWL fibril formation ( Figure 2B).…”
Section: ■ Resultsmentioning
confidence: 99%
“…30 By monitoring the kinetics of HEWL fibril formation by fluorescence spectroscopy, we found that the relative fluorescence of HEWL increased with extended incubation times (Figure 2A), which is in agreement with previous studies. 31 The consistent increase in ThT fluorescence intensity observed when HEWL was incubated alone, demonstrates that formation of amyloid fibrils proceeded rapidly and without a lag phase ( Figure 2A To determine an effective concentration range of myricetin for inhibiting HEWL fibril formation, varying aliquots of myricetin were mixed with HEWL to final concentrations of 1, 10, and 100 μM; at these concentrations we did not observe significant toxic effects of myricetin on cell survival (data not shown) and the ThT fluorescence intensity measured ( Figure 2B). Myricetin (and quercitin control) was observed to exhibit a dosedependent effect on HEWL fibril formation ( Figure 2B).…”
Section: ■ Resultsmentioning
confidence: 99%
“…The formation of Ab fibrils and oligomers requires a conformational change from an a-helix to a bsheet conformation, which is encouraged by the formation of a salt bridge between Asp 23 or Glu 22 and Lys 28. Recently, Cu 21 and various drugs used for AD treatment, such as galanthamine (Reminyl V R ), have been reported to inhibit the formation of Ab fibrils. However, the mechanism of this inhibition remains unclear.…”
mentioning
confidence: 99%
“…However, the mechanism of this inhibition remains unclear. Therefore, the aim of this work was to explore how Cu 21 and galanthamine prevent the formation of Ab 1-42 fibrils using molecular dynamics (MD) simulations (20 ns) and in vitro studies using fluorescence and circular dichroism (CD) spectroscopies. The MD simulations revealed that Ab 1-42 acquires a characteristic U-shape before the a-helix to b-sheet conformational change.…”
mentioning
confidence: 99%
See 2 more Smart Citations